(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This study evaluates how mindfulness-based treatments (MBIs) reduce nurse tiredness and improve patient care. The hard nature of nursing often causes stress and tiredness. This research examines how MBIs affect nurses’ mental health. Eleven studies are analyzed after reviewing the literature. MBIs may improve nurses’ mental health, according to the findings. Relaxation and mindfulness methods like meditation help nurses manage stress, exhaustion, and enhance health. MBI effectiveness was measured by stress, depressive disorders, anxiety, exhaustion, adaptability, quality of life, self-forgiveness, contentment, and mindfulness. The results show that mindfulness-based training may significantly lower nursing stress. They also reduce tiredness and improve mindfulness and self-compassion. Validated measures like the depression, anxiety, and stress scale help this research quantify outcomes. This investigation shows that MBIs can improve nurses’ mental health. Nurses may manage work stress and maximize job happiness by incorporating mindfulness techniques into their everyday routines. Thus, patient care and results may improve.